1993
DOI: 10.1530/jrf.0.0980293
|View full text |Cite
|
Sign up to set email alerts
|

Maturational changes in gonadotrophin secretion: the LH response to realimentation and a nocturnal increment in LH secretion of feed-restricted prepubertal gilts

Abstract: Potential maturational changes in patterns of LH secretion during feed restriction and the LH response to realimentation were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…At d 26 ± 1.3 of lactation, an indwelling jugular catheter was surgically implanted under general anesthesia via the cephalic vein (Cosgrove et al, 1993). On the day of blood sampling, feed was withheld during the first 2 h of sampling to allow for an estimate of preprandial insulin concentration.…”
Section: Blood Samplingmentioning
confidence: 99%
“…At d 26 ± 1.3 of lactation, an indwelling jugular catheter was surgically implanted under general anesthesia via the cephalic vein (Cosgrove et al, 1993). On the day of blood sampling, feed was withheld during the first 2 h of sampling to allow for an estimate of preprandial insulin concentration.…”
Section: Blood Samplingmentioning
confidence: 99%
“…Blood sampling An indwelling jugular cannula was surgically placed under general anaesthesia via the superficial cephalic vein (Cosgrove et al 1993) on day 9 of the study to facilitate stress-free, frequent blood sampling. On day 13, 10 ml heparinized blood samples were taken at 30-min intervals from 07.00 until 11.00 h and then hourly until 16.00 h. Plasma was obtained by centri¬ fugation of samples at 2000 g for 20 min immediately after collection and then stored in two aliquots per sample at -20°C until analysis for plasma insulin and IGF-I.…”
Section: Animalsmentioning
confidence: 99%
“…According to observations by Cosgrove et al (1993) the low farrowing rates indicate that pituitary support of the ovaries is at its weakest at the time when summer infertility is most frequent. Tast et al (2002) reported that the maternal factors that could be considered to cause the low farrowing rate are failure of sows to respond to embryonic signals, regression of the corpus luteum because of inappropriate luteinizing hormone (LH) secretion, or inadequate endometrial secretion interfering with normal development of embryos and their ability to produce the oestrogen signals when needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is significant that a decrease in LH concentration occurred at the same time as the frequency of disrupted fertility increased. However, the seasonal decrease in LH is not considered to be of sufficient magnitude to directly cause regression of the CL (Cosgrove et al, 1993;Peltoniemi et al, 1997b;Tast et al, 2001b). Although the seasonally diminished LH cannot directly cause regression of CL, it may decrease the progesterone secretion of the CL after it has become dependent upon pituitary LH support (Tast et al, 2002).…”
Section: Discussionmentioning
confidence: 99%